Una condición necesaria para la argumentación moral: La Situación Democrática. - González Delgado, Ángel Adrián (2013)
In this work we will study moral reasoning. The intended purpose is to clarify one of the features needed to understand this kind of reasoning, namely the framework of a democratic situation between debaters; toachieve it, some cases of moral dilemmas will be exemplified .